Blue Monday: Co-occurring Stimulant Use and HIV Persistence Predict Dysregulated Catecholamine Synthesis. (1st March 2021) - Chahine, Antonio; Koru-Sengul, Tulay; Feaster, Daniel J.; Dilworth, Samantha E.; Antoni, Michael H.; Klatt, Nichole; Roach, Margaret E.; Pallikkuth, Suresh; Sharkey, Mark; Salinas, Jessica; Stevenson, Mario; Pahwa, Savita; et al.
Abstract : Background: This longitudinal study examined whether co-occurring stimulant use and HIV disease processes predicted greater risk for depression via dysregulated metabolism of amino acid precursors for neurotransmitters. Methods: In total, 110 sexual minority men (ie, gay, bisexual, and other men who have sex with men) living with HIV who had biologically confirmed recent methamphetamine use were enrolled in a randomized controlled trial. The kynurenine/tryptophan (K/T) and phenylalanine/tyrosine (P/T) ratios were measured over 15 months to index dysregulated metabolism of amino acid precursors for serotonin and catecholamines. Markers of gut-immune dysregulation such as lipopolysaccharide binding protein and soluble CD14 (sCD14), HIV persistence in immune cells (ie, proviral HIV DNA), and stimulant use were examined as predictors. These bio-behavioral measures, including the K/T and P/T ratios, were also examined as predictors of greater risk for depression over 15 months. Results: Higher time-varying sCD14 levels (β = 0.13; P = 0.04) and time-varying detectable viral loads (β = 0.71; P < 0.001) were independent predictors of a higher K/T ratio. Time-varying reactive urine toxicology results for stimulants (β = 0.53; P < 0.001) and greater proviral HIV DNA at baseline (β = 0.34; P < 0.001) independently predicted an increased P/T ratio. Greater time-varying, self-reported methamphetamine use uniquely predicted higher odds of screening positive for depression (Adjusted Odds Ratio = 1.08; 95% confidence interval: 1.01 to 1.17). Conclusions: Ongoing stimulant use and HIV persistence independently predict dysregulated metabolism of amino acid precursors for catecholamines, but this did not explain amplified risk for depression.